Isolates Application of Multi-Functional Finishes on Denim Garments (Daffodil International University Journal of Science and Technology, 2012)
The main aim of this research is to apply the functional finishes to denim garments to enhance the value of the garment. The fabric selected for the research is 100% cotton with the construction of 2/1 Right Hand Twill. The selected fabric was made into garments (A-line frock) and subjected to de-sizing and enzyme washing and then the garments were treated with two different synthetic scents sweet citrus and rose oils to induce fragrance. The garments were also tested for the efficacy of anti-microbial, antifungal, UV protection, stain repellency and mosquito repellency finishes. The results have proven very good sense of functional finishes on to the garments in conjunction with a sweet fragrance. Two different methods – dip dry and micro encapsulation methods were chosen for the study and the fastness property of the finishes were compared. The treated garments were evaluated using AATCC standards. Keywords: fragrance finish; anti-microbial finish; anti-fungal finish; A-line frock; enzyme washing.   DOI: http://dx.doi.org/10.3329/diujst.v7i1.9649   Daffodil International University Journal of Science and Technology Vol.7(1) 2012 59-66